2013
DOI: 10.1371/journal.pone.0067115
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Exposure during Sensitization to Blomia tropicalis Allergens Shifts TH2 Immunity Towards a TH17-Mediated Airway Neutrophilic Inflammation: Role of TLR4 and TLR2

Abstract: Experimental evidence and epidemiological studies indicate that exposure to endotoxin lipopolysaccharide (eLPS) or other TLR agonists prevent asthma. We have previously shown in the OVA-model of asthma that eLPS administration during alum-based allergen sensitization blocked the development of lung TH2 immune responses via MyD88 pathway and IL-12/IFN-γ axis. In the present work we determined the effect of eLPS exposure during sensitization to a natural airborne allergen extract derived from the house dust mite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 47 publications
5
28
0
2
Order By: Relevance
“…Previous work of our group using the OVA‐model showed that the absorption of endotoxin LPS to alum adjuvant during the sensitization phase inhibited the development of Th2 responses, including IgE production . However, using B. tropicalis as allergen, the adsorption of endotoxin induced a neutrophilic lung inflammation . The activation of TLRs by endotoxin LPS in the OVA model dampened Th2 immunity without shifting toward Th1/Th17 immunity while in the B. tropicalis model it was observed a shift from Th2 toward a Th1/Th17 mediated lung inflammation .…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous work of our group using the OVA‐model showed that the absorption of endotoxin LPS to alum adjuvant during the sensitization phase inhibited the development of Th2 responses, including IgE production . However, using B. tropicalis as allergen, the adsorption of endotoxin induced a neutrophilic lung inflammation . The activation of TLRs by endotoxin LPS in the OVA model dampened Th2 immunity without shifting toward Th1/Th17 immunity while in the B. tropicalis model it was observed a shift from Th2 toward a Th1/Th17 mediated lung inflammation .…”
Section: Introductionmentioning
confidence: 81%
“…However, using B. tropicalis as allergen, the adsorption of endotoxin induced a neutrophilic lung inflammation . The activation of TLRs by endotoxin LPS in the OVA model dampened Th2 immunity without shifting toward Th1/Th17 immunity while in the B. tropicalis model it was observed a shift from Th2 toward a Th1/Th17 mediated lung inflammation . More recently, we have shown that CpG‐ODN, a TLR9 agonist, during sensitization to OVA was the most effective TLR agonist in attenuating Th2‐mediated allergic responses.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further supporting a role of human FetA in patients with allergic inflammation, the latter was found to increase TLR4 activation by grass pollen or house dust mite extracts, which are known to contain both allergens and endotoxins. 29,30,50 Interestingly, this synergistic activation of the TLR4 pathway was largely diminished for neuraminidase-treated FetA, highlighting the key role of sialic acids branched on glycans in this proallergic cascade. In agreement with the recent identification of FetA as a central adaptor molecule contributing to fatty acid-mediated inflammation, our study confirms the capacity of FetA to interact with the TLR4 pathway and induce nuclear factor kB (NF-kB)-driven genes.…”
Section: Discussionmentioning
confidence: 98%
“…Such vaccination is believed to exert its beneficial effects on the immune system, at least in part, by modifying the T-helper (T H )-2 lymphocyte response to subsequent natural allergen exposure. The use of T H 1 promoting adjuvants in allergen-specific vaccines seems to be beneficial in allergic humans and animal models of allergic diseases (Pfaar et al 2012;Barboza et al 2013;Kun and Li 2016;Mohammadi-Shahrokhi et al 2017), and it is coherent with the anti-allergic effect of natural exposure to T H 1 microbial stimuli, promoting the so-called T H 1 deviation (Debarry et al 2007;Romagnani 2014). In addition, the use of immunopotentiating adjuvants has a potential to reduce the allergen content in the vaccine and ameliorate its safety.…”
Section: Introductionmentioning
confidence: 99%